Self-Efficacy Levels Among Profession Nursing Students in Performing Basic Clinical Skills - Aprilia, Rahmita Nurul; Agustina, Hana Rizmadewi; Pratiwi, Sri Hartati (Indonesian Journal of Global Health Research, 2024)
Nursing profession’s education is responsible for preparing competent graduates ready to face healthcare challenges. A key indicator of this readiness is the self-efficacy of nursing students, which reflects their confidence in applying clinical skills. It is crucial for these students to be prepared to provide safe, high-quality care as they enter the workforce. This study aims to evaluate the self-efficacy levels in clinical skills among students enrolled in the Nursing Profession Study Program at the Faculty of Nursing, Universitas Padjadjaran. This study employed a quantitative descriptive method using a cross-sectional approach. The population in this study amounted to 150 active students of the Nursing Profession Study Program at the Universitas Padjadjaran and the sample was taken using total sampling type. Data was collected using the Clinical Skills Self-Efficacy Scale (CSES) to measure the level of self-efficacy in performing clinical skills with validity test results after translated to Bahasa ranging from 0.415-0.727, and the reliability test results 0.825. Univariate analysis was carried out using descriptive statistics. The results of the study show that students of the Nursing Professional Education Program at the Faculty of Nursing, Universitas Padjadjaran, have a high level of self-efficacy in performing basic clinical skills, with 80 students (53.3%) demonstrating high self-efficacy. Where the percentage of class 46 students who have a high level of self-efficacy is greater than class 47. This is largely due to the experience they have in carrying out clinical procedures. That’s related to the statement one of the main factors that can influence self-efficacy according to Albert Bandura is experience, the experience of someone who is successful in carrying out a task or achieving a goal can increase self-efficacy.